Staying on track. Recognition of overtraining syndrome in endurance athletes - Detmer, A. (Techniques Magazine, 2013)
The purpose of this paper is to give athletes and coaches a better understanding of the components of successful training, how OT accumulates and escalates without proper recovery, and the observable and physiological signs and symptoms of OTS. Having a better sense for all of these consequences can prevent OTS and performance pitfalls. Further research is needed with OTS; information on how it affects performance is lacking and most researchers seem stuck on trying to find the one marker to diagnose OTS. As shown in this paper, there are almost infinite responses as a consequence of OTS and not all individuals experience the same symptoms. Meur et al. is one of the few studies to take a multidisciplinary approach to detecting OTS, understanding, that there are several variables involved in the process (17). It would be of interest to see more research like this done in future studies. Nevertheless, there are promising methods being developed to test for the training status of an individual. If these tests are unavailable to the athlete and coach, however, much can be gained from simply recognizing signs and symptoms of OTS.